FUZZY CONTROLLER DESIGN FOR NONLINEAR SYSTEMS - Priyo, Sasongko Sidik (MATEMATIKA, 2008)
In this article is studied problem of Fuzzy Controller Design For Nonlinear Systems With Case Study Of  TORA System. Fuzzy control for nonlinear systems is proposed on the  framework from model of Takagi-Sugeno fuzzy model and PDC(paralel distributed compensation) controller. A lyapanouv-based stabilizing fuzzy control design for nonlinear systems using  Takagi-Sugeno fuzzy models is applied. The stability analysis and control design problems are reduced to  linear of matrix inequality (LMI) problems. So that method of fuzzy controller design are solve a set of LMI. Approach of PDC, robust and optimal controller are applied to  a  nonlinear control benchmark problem with case study  of TORA system. The designed fuzzy controllers are yield an asymtotic stable closed-loop system. The fuzzy controller  Simulation results are given to ilustrate the utility of the present fuzzy control.